Physicochemical Properties of Isosceles Triangle Plants Soil in Coastal Region of Mempawah Hilir Subdistrict - Suhaimi; Suryadi, Uray Edi; Yulies, Uray Suci; Indrawati, Vitri (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Isosceles Triangle Plants (ITP) are wave-breaking and sediment-trapping structures with a triangular shape, arranged continuously in a zigzag pattern and made of bamboo. Mangrove rehabilitation in Sengkubang Village has been carried out independently by planting Rhizophora stylosa Griff mangrove species. This study aims to examine the physicochemical properties of soil both inside and outside the ITP structures. The study results showed that redox potential varied, with both positive and negative values. Salinity ranged from 5.228 to 5.257 mmhos/cm on the outside and from 4.971 to 5.657 mmhos/cm on the inside. Total Dissolved Solids (TDS) were between 2,754 ppm and 2,971 ppm. Organic matter content ranged from 2.754% to 2.971%. Soil acidity (pH) tended to be neutral to slightly alkaline, between 7.59 and 7.91. The soil fraction composition was dominated by silt (83.42% to 93.00%), followed by clay (6.64% to 16.24%) and sand (0.32% to 0.52%). All soil structures were massive. Soil bulk density ranged from 0.54 g/cm³ to 0.58 g/cm³. Total soil porosity was high, between 75.60% and 78.39%, as was the field capacity water content (74.36% to 77.32%).